Books as history the importance of books beyond their texts - Pearson, David 1955- (British Library and Oak Knoll Press, 2011)
"A material culture study focused on the importance of books as objects from the Middle Ages to present. Looks beyond content of books to other properties such as printing, binding, and annotation. Over 140 full-color illustrations, bibliography, and index. Revised edition includes new text and images"--Provided by publisher.